A human blood–arachnoid barrier atlas of transporters, receptors, enzymes, and tight junction and marker proteins: Comparison with dog and pig in absolute abundance. Issue 2 (17th March 2022) - Uchida, Yasuo; Takeuchi, Hina; Goto, Ryohei; Braun, Clemens; Fuchs, Holger; Ishiguro, Naoki; Takao, Masaki; Tano, Mitsutoshi; Terasaki, Tetsuya
Abstract: The purpose of this study was to elucidate the absolute abundance of transporters, enzymes, receptors, and tight junction and marker proteins at human blood–arachnoid barrier (BAB) and compare with those of dogs and pigs. Protein expression levels in plasma membrane fractions of brain leptomeninges were determined by quantitative targeted absolute proteomics. To realistically compare the absolute abundance of target molecules at the BAB among humans, dogs, and pigs, the unit was converted from fmol/μg‐protein to pmol/cm 2 ‐leptomeninges. Of a total of 70 proteins, 52 were detected. OAT1, OAT3, GLUT1, 4F2hc, EAAT1, EAAT2, MCT8, SMVT, CTL2, GFAP, Claudin‐5, Na + /K + ‐ATPase, COMT, GSTP1, and CES1 were abundantly expressed at the human BAB (>1 pmol/cm 2 ). The protein expression levels were within a 3‐fold difference for 16 out of 33 proteins between humans and dogs and for 13 out of 28 proteins between humans and pigs. Both human–dog and human–pig differences in protein expression levels were within 3‐fold for OAT1, OAT3, 4F2hc, xCT, OCT2, MDR1, BCRP, PEPT2, SYP, and MCT1. In contrast, OCT3, MCT4, and OATP1A2 were detected in humans but not in dogs or pigs. MRP3 was detected in dogs and pigs but not in humans. The absolute level of GLUT1 in humans was nearly the same as that in dogs but was 6.14‐fold greater in pigs. No significant differences in the levels were observed between male and female dogs for nearly all molecules. These results should be helpful in understanding the physiological roles of BAB and cerebrospinal fluid pharmacokinetics in humans and their differences from dogs and pigs. Abstract : This is the first paper comprehensively clarifying absolute protein expression levels of many transporters at a new central nervous system (CNS) barrier "blood‐arachnoid barrier" in humans, by means of quantitative Targeted Absolute Proteomics (qTAP) technique, without any antibody. The absolute protein expression levels of many transporters at the blood‐arachnoid barrier in humans were compared with those in dogs and pigs which are preclinical useful animals for drug discovery and development. These data first provide a better understanding about CNS concentrations/kinetics of endogenous bioactive compounds and drugs, which has not been understood by blood‐brain barrier study.